Organization of digital book exhibitions as a means for remote library service - Koval Tatiana; Smoliar Inessa; Turovska Lesia (Bìblìotečnij vìsnik, 2021)

(untitled)
Topic theme. Providing users with information on new arrivals to the funds of the V. I. Vernadskyi National Library of Ukraine in the format of digital exhibitions. The subject of research is digital exhibition activity as a creative means of remote library and information services. The aim of the research. Study of digital exhibitions in the system of remote library services on the example of a typical digital displaying of new arrivals to the VNLU funds. Methodology. Systemic, informational, structural-functional, comparative, historical, terminological approaches, as well as a set of general scientific, specific scientific and special methods. Scientific novelty. Further development of prospects on the organization of digital book exhibitions as a means of producing scientific knowledge and a tool for remote maintenance in the process of meeting the needs of remote users. Development of practical approaches to the organization of a typical digital showcase of new arrivals to the VNLU fund. Conclusions. The digital format of the organization of book exhibitions provides users with a number of exclusive opportunities, contributes to the achievement of a qualitatively new level of meeting the needs of readers. Having been uploaded on the Internet, the exhibition activity provides library and information service efficiency, scale of the audience, expansion of the range of availability of services. On the other hand, the organization of digital book exhibitions increases the information potential of the library funds, promotes its active development. Practical meaning. The article establishes typical methodological and technological solutions for the organization of digital exhibitions of the new arrivals to the VNLU funds; it determines the theoretical, methodological and technological bases of quality organization of digital exhibition activities; outlines the interactive capabilities of digital exhibitions of new arrivals to the VNLU funds as a new form of dialogue in the scientific communications environment.